Modelling of cloud effects of flammable gases and fumes - Stanković, P., Faculty of Occupational Safety, Niš (Serbia); Krstić, I., Faculty of Occupational Safety, Niš (Serbia); Mihajlović, E., Faculty of Occupational Safety, Niš (Serbia) (Facta Universitatis. Series. Working and Living Environmental Protection (Serbia), 2009)
During a technological process, either during regular work or in case of an accident, there is a possibility of a fire and explosion owing to hazardous liquids leaking and, flammable and explosive gases being produced. The impact on people and the environment is particularly emphasized when flammable and toxic fumes are formed. In this sense, the subject of the paper is the modelling and simulation of the effects occurring in those conditions with the purpose of designating a safe zone. Based on possible accident scenarios and using a mathematical model, it is possible to assess the ecological risk, where real-time models generate an image of dangerous areas.